Circulating Osteocalcin‐Positive Cells as a Novel Diagnostic Biomarker for Bone Metastasis in Breast Cancer Patients. (20th May 2020) - Lee, Kyung‐Hun; Lee, Kyoung Jin; Kim, Tae‐Yong; Hutomo, Febby; Sun, Hyun Jin; Cheon, Gi Jeong; Park, Serk In; Cho, Sun Wook; Im, Seock‐Ah
ABSTRACT: Current diagnosis of bone metastasis (BM) in breast cancer relies on structural changes of bone that occur only in the advanced stage. A sensitive biomarker for detecting early progression of bone metastasis is urgently required. We performed clinical and preclinical studies to investigate diagnostic value of circulating osteocalcin‐positive cells (cOC) in breast cancer bone metastasis. Metastatic breast cancer patients ( n = 92) with or without bone metastasis (ie, BM + or BM – ) were enrolled, and cOC were measured at enrollment. Patients were followed up for bone metastasis progression for 18 months. BM + patients ( n = 59) were divided into progressive (PD) or stable disease (SD) groups, based on imaging studies at the end of the 18‐month study. The PD group had higher baseline cOC compared with the SD group. Furthermore, higher cOC resulted in reduced BM progression‐free survival. Three patients in the BM – group ( n = 33) developed new BM during the 18‐month study, and these patients had a higher level of baseline cOC compared with the remaining BM – patients. In murine preclinical studies, cOC increased at early time points when micro‐metastases were evident only by histology but undetectable by bioluminescence imaging. Also, cOC levels predicted the progression of BM and correlated significantly with BM tumor burden. cOC increased in the early phase of breast cancer BM and can predict BM progression, supporting cOC as a potential novel biomarker. © 2020 American Society for Bone and Mineral Research.